The Humble Advice and earnest desires of certain well-affected ministers, lecturers of Banbury in the County of Oxon, and of Brackly in the County of Northampton To his Excellency Thomas Lord Fairfax, Generall of the Forces raised by the Authority of Parliament; and to the Generall Councell of VVare. : Presented Ianuray 25. 1649. by two of the Subscribers. : Also, a Letter to the Reverend Ministers of the Gospel within the Province of London, dated the 21 of this instant January. [electronic resource] :
Summary goes here